Cephalohematomas in children - A. F. Kiosov (Лечащий Врач)
According to world literature, the frequency of registration of cephalogemate in newborns is 0,2–4,0%. Cephalohematomas most often develop after applying vacuum extraction. Most subperiosteal hemorrhages in children are resolved on their own. In 2–5% of cases, resorption of cephalohematomas does not occur and complications may occur in the form of suppuration and calcination. Routine puncture and aspiration with cephalogemate in children should not be carried out.